Detailed analysis of the Japanese version of the Rapid Dementia Screening Test using Arabic‐hiragana conversion. - Moriyama, Yasushi; Yoshino, Aihide; Muramatsu, Taro; Mimura, Masaru (Psychogeriatrics, 2018)
Aim: The number‐transcoding task on the Japanese version of the Rapid Dementia Screening Test (RDST‐J) requires conversion between Arabic and Chinese numerals (209 to 二百九, 4054 to 四千五十四, 六百八十一 to 681, 二千二十七 to 2027). In this task, questions and answers are written for Chinese‐Arabic conversion. We reported that the RDST‐J could distinguish subjects with Alzheimer's disease with a Clinical Dementia Rating Scale score of 0.5 from controls. In this study, we investigated the impact of changing the task to a hiragana‐Arabic conversion. Methods: Participants consisted of 45 patients with a Clinical Dementia Rating Scale score of 0.5 and 52 normal controls. Results: The sensitivity and specificity of total scores ≥9 on the two RDST‐J versions for discriminating subjects with a Clinical Dementia Rating Scale score of 0.5 from controls were 73.1% and 75.5%, respectively, on the original version, and 71.8% and 73.0%, respectively, on the revised version. Conclusions: The sensitivity and specificity of the revised version of the RDST‐J was equivalent to those of the original version.